2022
DOI: 10.3390/ijerph191912019
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Mortality in Patients Aged 80 and over Residing in Nursing Homes—Six Pandemic Waves: OCTA-COVID Study

Abstract: During the first COVID-19 pandemic wave in Spain, 50% of deaths occurred in nursing homes, making it necessary for some hospitals to support these facilities with the care of infected patients. This study compares origin, characteristics, and mortality of patients admitted with COVID-19 during six pandemic waves in the Hospital Central de la Cruz Roja in Madrid. It is a retrospective observational study of patients ≥ 80 years old, admitted with an acute SARS-CoV-2 infection, with a total of 546 patients includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Our study, unlike others [ 19 , 36 , 37 ], shows no differences in mortality by sex during the first wave of COVID-19.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Our study, unlike others [ 19 , 36 , 37 ], shows no differences in mortality by sex during the first wave of COVID-19.…”
Section: Discussioncontrasting
confidence: 84%
“…A study among nursing home populations found higher mortality in the infected COVID-19 patients compared with the residents who were not infected with COVID-19, but not compared with the community population [ 29 ]. Another study showed higher mortality in the infected patients over 80 years of age in nursing homes than in the community patients, but only hospitalized patients were studied [ 36 ]. Another study showed higher mortality in nursing homes than in a community group control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the findings reported by Ruiz-Huerta et al . [ 23 ] in their study on 546 patients. Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that in this study, those patients who recovered and those who died from COVID-19 were age and gender matched. This is an important factor for the following reason: from the beginning of the pandemic [58] until the end of its six waves [59], disputes that concerned the higher risk of lethal outcome of a SARS-CoV-2 infection in elderly people, especially men, were common, while comorbidities and the variant of virus appeared to be more relevant predictive factors. However, the patients involved in this study had no comorbidities and were all hospitalized during the same wave of the pandemic in December 2020, so the obtained results do indeed reflect the differences associated with different outcomes of the severe disease itself.…”
Section: Discussionmentioning
confidence: 99%